Emerging investigator series: geochemistry of trace elements associated with Fe and Mn nodules in the sediment of limed boreal lakes. Issue 2 (23rd January 2018) - Couture, Raoul-Marie; Hindar, Atle; Rognerud, Sigurd
Abstract : We report on the geochemical legacy of the liming of acidified lakes in Norway. We document the occurrence of Fe–Mn nodules and the diagenetic redistribution of trace-elements at the sediment–water interface of limed boreal lakes. Abstract : Thousands of boreal lakes were limed for decades in Scandinavia to counteract the effect of anthropogenic acidification. We measured the concentrations of alkali earth metals (Ca, Mg, Ba), metals (Mn, Fe, Al, Co, Cd, Pb, Zn), metalloids (As, Mo) and phosphorus (P) in 165 surface sediment samples from 17 limed lakes, as well as the sediment column and porewater of two lakes chosen from this set. We report that formation of ferromanganese nodules is widespread in limed lakes, and that those nodules are enriched in trace elements, reaching for example 11 500, 908 and 40 μg g −1 for Ba, Mo and As, respectively. Nodules are more abundant between the littoral and the profundal zones. Intense redox cycling of Fe and Mn at the sediment–water interface has redistributed trace elements in the sediment column. Ba, Co, Mo, Pb and Zn partitioned with Mn (oxy)hydroxides and As and P with Fe (oxy)hydroxides. Fe, Mo, Co and As remobilized to the porewater also diffused downward and were likely sequestrated with sulfides. We conclude that the diagenetic redistribution and partitioning of trace elements onto Fe–Mn nodules, rather than direct inputs from liming, is the cause of the elevated trace element burden in surface sediments.